Gender identity of senior school students as a factor in the implementation of a gender approach in physical education - Marchenko , Oksana; Rostov , Oleh; Brychuk, Mariia (Sportyvnyi Visnyk Prydniprovia, 2026)
Introduction. The implementation of a gender-sensitive approach in physical education of senior school students requires consideration of their individual characteristics, particularly the type of gender identity, which determines the specificity of motivation for physical activity and the need for physical self-improvement. Senior school age represents a sensitive period of personality development, formation of value orientations, and behavioral strategies, which highlights the relevance of a scientifically grounded gender-sensitive approach to organizing physical education. Purpose. To identify types of gender identity of senior school students as a factor in the implementation of a gender-sensitive approach in physical education. Methods. The study employed theoretical methods (analysis of scientific and methodological literature), psychodiagnostic methods (Sandra Bem’s Masculinity–Femininity questionnaire — Bem Sex Role Inventory), as well as methods of mathematical statistics (analysis of variance, post hoc comparisons) and cluster analysis to identify gender identity types and to construct their psychological profiles. Statistical data processing was performed using MS Excel and Statistica 10.0 (StatSoft, USA). Results. The study identified four types of gender identity among senior school students: feminine, masculine, androgynous, and undifferentiated. A statistically uneven distribution of students across the identified types was revealed, with a predominance of the undifferentiated type. Twelve stable personality traits-discriminators (7 instrumental and 5 expressive) were identified, which significantly differentiate the gender identity types and form distinct psychological profiles for each type. Conclusions. The types of gender identity of senior school students are characterized by different combinations of instrumental and expressive traits, which determine differences in motivation for physical activity and physical self-improvement. Taking these characteristics into account is an important condition for the effective implementation of a gender-sensitive approach in physical education and provides a basis for differentiating pedagogical strategies with regard to students’ psychological characteristics.